Application of multimedia in language self-learner - Nooh, Athifah Nafhah; Hassan Abdalla Hashim, Aisha; Zeki, Akram M. (IIUM Press, 2015)
Multimedia courseware is a software developed for educational purposes. Nowadays, learning to speak more than two languages gives one a good edge over others. This chapter discusses how to create a courseware that can help user to learn three different languages at one time. The courseware can improve the limitations of existing products. The courseware is basically a language self-learner that consists of Mandarin, Japanese and Korean languages. It uses English language to assist the user. It will also provide the visual, Kanji, Romanji and audio of the word. So, users can actually hear the correct pronunciation of the word, learn to write the Kanji of the word, and get many benefits by using this courseware.